Knowledge and practice of first aid on burns among parents in Hospital Universiti Sains Malaysia, Kelantan - Rejab, Rahimah Mat (Universiti Sains Malaysia, 2015)
The purpose of this cross-sectional study was to determine the Knowledge and Practices of First Aid on Burns among parents in Hospital Universiti Sains Malaysia (USM). The health belief model was used as theoretical framework of the study. Self-administered questionnaire was used and 124 subjects were recruited in this study. Before they enrolled in this study, subjects were consented and being informed about the protocol of the study. A pilot study had been done among 30 subjects to check the reliability and validity of the study. Score of knowledge of first aid on burns was evaluated during the data analysis. The Pearson’s Chi- Square test was used to test whether there was any significant association between score of knowledge of first aid on bums with selected demographic data (age, gender, and level of education) and with previous aid training. The common practices of first aid on burns with traditional and herbal practices as first aid also being tested in this study. From this study, score of knowledge of first aid on burns among parents in Hospital USM were at contraindicated score (38.7%). Significant association was found between the knowledge of first aid on bums with the previous training. The most practices that been used as first aid on bums was by using running water on the burn injury but there’s still that used toothpaste that apply on the burns injury as first aid on burns before seek for medical treatment. There is a need for health care professionals to empower the public on knowledge and practices of first aid on bums because bum injury sometimes occurs at home or at working area. It is hoped that this study will help to expand the knowledge and serve as reference to help in improving the management of first aid on bums in Malaysia, as well as improve in nursing service and related research.